Senso de coerência e desfechos em saúde bucal em jovens do Exército Brasileiro - Lock, Nicássia Cioquetta (2022)
This thesis is composed of three scientific articles whose objectives were: (1) to analyze the association between sense of coherence (SoC) and flossing (Article I); (2) to study the association between SoC and caries activity (Article II); and (3) to evaluate the association between SoC and oral health-related quality of life (OHRQoL) (Article III) in young people aged 18-19 years who joined the Brazilian Army as enlisted for mandatory military service in two military bases located in southern Brazil. 520 adolescents were evaluated between the years 2019-2021. Data collection included the application of questionnaires and clinical oral examination. A structured questionnaire gathered data on sociodemographic information (adolescent's education and family income) and oral health-related habits (use of dental floss and whether the participant had visited the dentist for preventive purposes in the previous year). OHRQoL was collected using the Oral Health Impact Profile-14 questionnaire. Adolescent‟s SoC was assessed using the validated Brazilian version of the SOC-13 scale. The primary outcomes of Articles I, II and III were, respectively, flossing, caries activity, and OHQQoL. In all articles, SoC was considered the main predictor variable, categorized as low, moderate, or high, based on tertiles. Preliminary analyzes were performed to compare outcomes according to predictor variables using the Wald test. The association between predictor variables and outcomes was assessed using Poisson regression models (unadjusted and adjusted), and prevalence ratios (PR) and rate ratios (RR) were estimated, as well as their 95% respective confidence intervals (CI). In Article I, the prevalence of flossing was significantly higher in adolescents with high SoC (41.2%) than in those with low SoC (29.2%). Adolescents with high SoC were 45% more likely to floss than those with low SoC (adjusted PR = 1.43; 95% CI = 1.06-1.93). In Article II, the prevalence of caries activity was 73.2% and, on average, adolescents had 2.45 active caries lesions. High SoC was associated with a lower extent of caries activity (adjusted RR = 0.85; 95% CI = 0.74-0.98), with no association with the prevalence of caries activity. In Article III, it was observed that adolescents with moderate and high SoC had, respectively, mean OHIP-14 scores o27% (adjusted RR = 0.73; 95% CI = 0.64-0.84) and 49% (adjusted RR = 0.51; 95% CI = 0.43-0.59) lower than those with low SoC. SoC and family income remained significantly associated with OHRQoL even after the inclusion of behavioral and clinical variables. This thesis concluded that there is a significant association between SoC and flossing (Article I), number of active caries lesions (II), and OHRQoL (III) among 18- to 19-year-old recruits from southern Brazil.